PROFIL STATISTIK PENDIDIKAN ANAK BERKEBUTUHAN KHUSUS DI SEKOLAH INKLUSIF - Nadia Afsari; Maulidiah; Iki Yusran (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to describe the statistical profile of education for Children with Special Needs (CSN) in inclusive schools in Indonesia. Using a qualitative approach with a literature study method, the research analyzes data related to student distribution, types of special needs, educational levels, services, and the distribution of inclusive schools. The results show that inclusive education has a positive impact on the social, emotional, and academic development of CSN while fostering empathy, tolerance, and inclusiveness among regular students. However, its implementation still faces several challenges, such as a shortage of special education teachers, inadequate facilities, and incomplete curriculum adaptation. Therefore, teacher training in identifying and addressing diverse student needs, strengthening educational policies, and improving infrastructure are essential to achieving high-quality, equitable, and sustainable inclusive education based on educational statistical data.